Distribution and Habitat Use by Asian Elephants (Elephas maximus) in a Coffee-Dominated Landscape of Southern India. (January 2019) - Krishnan, Vinod; Kumar, Mavatur Ananda; Raghunathan, Ganesh; Vijayakrishnan, Sreedhar
Understanding the impacts of land-use mosaics on elephant distribution and the patterns of habitat use is essential for their conservation in modified landscapes. We carried out a study in 205 villages, covering 610 km 2 of plantation–agriculture–forest mosaic of Hassan–Madikeri divisions in southern India, an area of intense human–elephant interactions. We monitored elephant movements, crop damage incidents, and human casualties on a daily basis for a 2-year period (2015–2017) to understand the patterns of elephant distribution across the landscape and habitat-use patterns, resulting in 1, 117 GPS locations across six major habitats. Elephants were distributed across the landscape in the first year, but a high concentration of locations were noticed toward northern part of the study area during the second year, owing to clear felling of trees and installation of barriers around coffee plantations, causing an overall shift in their distribution. Investigations into habitat use by elephants revealed that during the day, elephants preferred monoculture refuges of acacia, eucalyptus, and so on, and forest fragments, avoiding reservoir, coffee, roads, and habitations. At night, agricultural lands were used more frequently while moving between refuges compared with forest fragments and habitations. Seasonally, forest fragments and agriculture were used significantly more during dry and wet, respectively. Across years, use of monoculture refuges and coffee increased with a corresponding decrease in the use of forest fragments and agriculture. In areas devoid of forest habitats, retention of monoculture refuges which provide shelter for elephants and facilitating free movement through open habitats may help minimize human–elephant conflict and promote coexistence in such land-use mosaics.